Assessment of organic carbon contamination in the unsaturated zone: a case of Yogyakarta City, Indonesia - Heru Hendrayana; Doni Prakasa Eka Putra; Yosua Priambodo (Brawijaya University, 2021)
In 1997, groundwater pollution was caused by a diesel leak at the Yogyakarta City Railway Station. People in the south of the railway station discovered the presence of diesel in dug wells in 2001. The existing diesel is still found in dug wells even though the pollutant source had been removed. The current source of pollution comes from diesel residues trapped in the unsaturated zone. Understanding the distribution and concentration of diesel in the unsaturated zone is the goal of this study. In this study, diesel concentration was measured based on Total Organic Carbon (TOC) levels. The research was conducted through shallow core and deep core drillings. Shallow core drilling was done at 14 points with a depth of 50 cm, and deep core drilling was done at nine drilling points with a depth of 15-17 m. 14 shallow core drilling samples were taken from a depth of 30 and 50 cm and nine deep core drilling samples were taken from a depth of 4-5 m and 10-11 m. The lithology logs in both drills were tested for diesel odour and TOC levels using the Soli TOC tool. Based on the test results, the smell of diesel was found at a depth of 10 to 15 m. TOC levels in the unsaturated zone ranged from 340 to 90,870 mg/L. TOC levels >30,000 mg/L were dominant at shallow depths even though they did not smell like diesel. At a location close to the source of the diesel tank leak at a depth of 4-5 m, the measured TOC level was 30,100 mg/L. The results showed that there were zones of high TOC levels associated with diesel odour layers. The zones existed because of the infiltration and percolation processes that had carried surface water and diesel pollutants and eventually moved horizontally following groundwater flow.